Dexamethasone protected human glioblastoma U87MG cells from temozolomide induced apoptosis by maintaining Bax:Bcl-2 ratio and preventing proteolytic activities - Das, Arabinda (BioMed Central, 2004)
BACKGROUND: Glioblastoma is the deadliest and most prevalent brain tumor. Dexamethasone (DXM) is a commonly used steroid for treating glioblastoma patients for alleviation of vasogenic edema and pain prior to treatment with chemotherapeutic drugs. Temozolomide (TMZ), an alkylating agent, has recently been introduced in clinical trials for treating glioblastoma. Here, we evaluated the modulatory effect of DXM on TMZ induced apoptosis in human glioblastoma U87MG cells. RESULTS: Freshly grown cells were treated with different doses of DXM or TMZ for 6 h followed by incubation in a drug-free medium for 48 h. Wright staining and ApopTag assay showed no apoptosis in cells treated with 40 μM DXM but considerable amounts of apoptosis in cells treated with 100 μM TMZ. Apoptosis in TMZ treated cells was associated with an increase in intracellular free [Ca(2+)], as determined by fura-2 assay. Western blot analyses showed alternations in the levels of Bax (pro-apoptotic) and Bcl-2 (anti-apoptotic) proteins resulting in increased Bax:Bcl-2 ratio in TMZ treated cells. Western blot analyses also detected overexpression of calpain and caspase-3, which cleaved 270 kD α-spectrin at specific sites for generation of 145 and 120 kD spectrin break down products (SBDPs), respectively. However, 1-h pretreatment of cells with 40 μM DXM dramatically decreased TMZ induced apoptosis, decreasing Bax:Bcl-2 ratio and SBDPs. CONCLUSION: Our results revealed an antagonistic effect of DXM on TMZ induced apoptosis in human glioblastoma U87MG cells, implying that treatment of glioblastoma patients with DXM prior to chemotherapy with TMZ might result in an undesirable clinical outcome.